Decision Support System For The Specification Of The Best Quality Corn Kernels With Multi Attribute Utility Theory Method - Imam, Chairul (SEAN Institute, 2024)
Farmers sell corn kernels to the company PT Charoen Pokphan Indonesia Tbk Medan, the corn kernels are used for a mixture of feed raw materials in order to fulfill the protein and nutritional value of the feed to be of quality. The company PT Charoen Pokphan Indonesia Tbk Medan buys corn seeds to farmers with the best quality corn seed specifications, so that they know the total price of the corn seeds according to the quality needed. This research determines the criteria for the best quality corn kernels and how to apply the Multi Attribute Utlity Theory Method to the decision support system to determine the quality of these corn kernels, to be able to help the company PT charoen pokphan indonesia tbk Medan in determining the quality of corn kernels. Based on the criteria that have been set at the company PT Charoen Pokphan Indonesia Tbk Medan to get the best quality corn seed value using grade 1 to grade 4 and ranking. The result of testing these methods is that a decision is made on an alternative with a total value of 86.7%. So this method is needed to evaluate the determination of the best quality corn kernel specifications so as to produce the best decision